2011
DOI: 10.1172/jci45963
|View full text |Cite
|
Sign up to set email alerts
|

T cell killing by tolerogenic dendritic cells protects mice from allergy

Abstract: It is well established that allergy development can be prevented by repeated low-dose exposure to contact allergens. Exactly which immune mechanisms are responsible for this so-called low zone tolerance (LZT) is not clear, although CD8 + suppressor T cells are known to have a role. Here, we show that TNF released by tolerogenic CD11 + CD8 + DCs located in skin-draining lymph nodes is required and sufficient for development of tolerance to contact allergens in mice. DC-derived TNF protected mice from contact al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 55 publications
3
27
0
1
Order By: Relevance
“…In these earlier studies, many and diverse mechanisms of action were suggested, including immune-specific tolerance through the induction of T-regulatory cells, IL-10 secretion, and IL-2 inhibition 3,9,12,37 ; nonspecific inhibition through the NO system 10,38-40 ; inhibition via indoleamine 2,3-dioxygenase 37,41 ; and apoptosis through death receptors including Fas, TRAIL, and TNF. [13][14][15]17,39,42,43 Likewise, our results suggest that BM-derived DCs obtained after culturing of whole BM with either GM-CSF (supplemental Figure 4) or FLT3 ligand 44 (supplemental Figure 5) do not exhibit detectable levels of perforin or appreciable killing of cognate 2C CD8 T cells. Therefore, our results suggest that the perforin ϩ imDCs grown in our study from purified HSCs represent a novel subpopulation found in a small percentage in the spleen under steady state, which nevertheless can expand in the spleen after GM-CSF administration in vivo.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In these earlier studies, many and diverse mechanisms of action were suggested, including immune-specific tolerance through the induction of T-regulatory cells, IL-10 secretion, and IL-2 inhibition 3,9,12,37 ; nonspecific inhibition through the NO system 10,38-40 ; inhibition via indoleamine 2,3-dioxygenase 37,41 ; and apoptosis through death receptors including Fas, TRAIL, and TNF. [13][14][15]17,39,42,43 Likewise, our results suggest that BM-derived DCs obtained after culturing of whole BM with either GM-CSF (supplemental Figure 4) or FLT3 ligand 44 (supplemental Figure 5) do not exhibit detectable levels of perforin or appreciable killing of cognate 2C CD8 T cells. Therefore, our results suggest that the perforin ϩ imDCs grown in our study from purified HSCs represent a novel subpopulation found in a small percentage in the spleen under steady state, which nevertheless can expand in the spleen after GM-CSF administration in vivo.…”
Section: Discussionmentioning
confidence: 70%
“…This is in contrast to the killing exerted by tolerogenic CD11c CD8 ϩ mature DCs shown to be dependent on TNF-␣. 14 These results and the rapid nature of the killing observed, strongly suggested the possibility that a perforinmediated mechanism might mediate the deletion of the alloreactive CD8 ϩ T cells by the imDCs. To further address this point, we first tested the expression of perforin in imDCs by immunostaining ( Figure 3A) and by Western blotting ( Figure 3B).…”
Section: Mhc-dependent Killing Of Cd8 ؉ Effector T Cells By Imdcs Is mentioning
confidence: 90%
See 1 more Smart Citation
“…In particular, research has focused on the generation of tolerogenic DCs (TolDCs) capable of modulating antigen-specific immune responses (6, 7). TolDCs may induce antigen-specific tolerance through induction of anergy, deletion of auto-reactive T cells (8, 9), generation and expansion of regulatory T cells (Treg) (10, 11), and/or the establishment of an anti-inflammatory environment through secretion of IL-10 and/or transforming growth factor beta (TGF-β) (12). …”
Section: Introductionmentioning
confidence: 99%
“…We have show refractoriness of PBMCs to rechallenged DM using 2 methods: preconditioning with MSCs and repeated exposure to low-dose DM and MSCs (Figs 5 and 6). Other studies have reported on killing of T cells by tolerogenic DCs, 44 which could be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%